Large Scale LoRa Networks: From Homogeneous to Heterogeneous Deployments - Ochoa M.N. (2018)
The work has been partly funded by the European Union Horizon 2020 research and innovation program under grant agreement No. 761745, the Government of Taiwan and by Cienciactiva-CONCYTEC of the Peruvian government